Pengaruh Rasio Crude Enzim Selulase Trichoderma reesei dan Aspergillus niger terhadap Kadar Gula dan Bioetanol Fermentasi Kulit Kacang Tanah (Arachis hypogaea L.) Menggunakan Zymomonas mobilis - Trianik Widyaningrum; A’isyah Arroobi’atu Rizqiyah (Bioscientist : Jurnal Ilmiah Biologi, 2023)
The need for fuel oil in Indonesia is increasing along with the increase in the number of people's consumption in the fields of transportation, industry, and economy. While the source of petroleum fuel in Indonesia is running low. Therefore, it is necessary to utilize alternative energy, namely bioethanol. Bioethanol can be produced from organic waste that contains high cellulose, one of which is peanut shells. This study aims to determine the effect of the ratio of crude cellulase enzyme Trichoderma reesei and Aspergillus niger on sugar and ethanol content of peanut shell fermentation using Zymomonas mobilis, and to determine the ratio of crude cellulase enzyme that produces the highest sugar and ethanol content of peanut shell fermentation using Z. mobilis. This research is an experimental study with independent variables, namely the ratio of crude cellulase enzyme T. reesei : A. niger (0:0), (1:0), (0:1), (1:1), (1:2), (2:1), (1:3), and (3:1) and the dependent variable of sugar and biethanol content. Data analysis of experimental research results using ANOVA and DMRT test. The addition of crude cellulase enzyme from T. reesei and A. niger affects the sugar content and bioethanol from peanut shell fermentation. The ratio of crude cellulase enzyme from T. reesei and A. niger that produces the highest sugar content is in the treatment P5 ratio of crude enzyme T. reesei: A. niger (2:1) which is 0.14 g/mL and the highest ethanol content from groundnut shell fermentation is in the treatment of P8 crude enzyme ratio of T. reesei : A. niger (1:3) which is 2.23%.